Carbon Ligands From Fundamental Aspects to Applications - Canac, Yves (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Homogeneous catalysis owes its success, in large part, to the development of a wide range of ligands with well-defined electronic and steric properties, which have thus made it possible to adjust the behavior of many organometallic complexes. However, ligands used in catalysis have long been centered on elements of group 15, and it is only more recently that carbon ligands have proved to be valuable alternatives with the emergence of cyclic diaminocarbenes (NHC).This Special Issue aims to provide a contemporary overview of the advances in carbon ligand chemistry from fundamental aspects to applications.